State regulation of housing building in ukraine in the context of economic cycle - Fedun, I. (Ways to Improve Construction Efficiency, 2018)
The article is devoted to the development of the concept of state regulation of housing construction in the context of economic cyclicality. The influence of economic cycles on the indicators of housing development in Ukraine is investigated. The expediency of state regulation of housing construction in the conditions of economic cyclicalness is substantiated and its targets are defined depending on the phase of the economic cycle. An indicative list of economic policy measures of the state that can be implemented in the process of state regulation of housing construction in terms of economic cyclicality is offered.